Desain System Smart Clothesline Berbasis Arduino Dengan Metode Logika Fuzzy - Joni Eka Candra; Very Karnadi (LPPM Universitas Putera Batam, 2018)
Drying clothes is one activity that moften done in household life. Batam islands almost rainfall throughout the year and the people of Batam City are working in the industrial and government sectors indirectly often outside the house so that the activities of drying clothes left abandoned or working, so become it rains or when the night come can not lift clothesline. Based on these problems the researcher wishes to design and build a system that can work automatically by using arduino uno R3 as control system and fuzzy logic method mamdani as logic control system and utilizing water sensors and LDR sensors as input data from the outside environment in case of change. Based on the result of testing of smart clothesline system based on Arduino using fuzzy logic method can be concluded that the system has been in accordance with the rule base created using fuzzy mamdani logic approach. That servo motors can move from angle 0˚ to angle 90˚, which means to move close when the water sensor exposed to water (rain) and LDR sensor when not exposed to light (night), and servo motors can move from corner 90˚ to corner 0 ˚ which means moving open when the dry water sensor (Heat) and the LDR sensor are exposed to light (Daylight).